The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1159/000176695
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Left Ventricular Mass and Filling after Renal Transplantation Are Related to Changes in Blood Pressure: An Echocardiographic and Pulsed Doppler Study

Abstract: To examine changes in left ventricular (LV) mass and function (diastolic and systolic) after successful renal allograft transplantation (RT), we prospectively studied 30 patients (19 men, 11 women, aged 37 ± 13 years) by M-mode, two-dimensional and pulsed Doppler echocardiography at the time of surgery and 10 ± 1.8 months later. At the time of transplantation all patients had been undergoing dialysis (4 peritoneal dialysis, 26 hemodialysis) for 2.5 ± 3.2 years. A hematocrit of ≤30% was present in 26 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 19 publications
2
30
1
Order By: Relevance
“…In dialysis patients with a long-term AV fistula, Ponsin et al [5]reported a significant correlation between the signs of cardiac insufficiency and the fistula blood flow × fistula duration product. In two recent reports on renal transplant patients with normal or near-normal cardiac function, however, the persistence of an AV fistula did not influence LV mass or other echocardiographic parameters [2, 3]. We found that the persistence of even large, high-flow AV fistulas for prolonged periods of time did not significantly influence the LV mass and had little impact on cardiac morphology and function.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In dialysis patients with a long-term AV fistula, Ponsin et al [5]reported a significant correlation between the signs of cardiac insufficiency and the fistula blood flow × fistula duration product. In two recent reports on renal transplant patients with normal or near-normal cardiac function, however, the persistence of an AV fistula did not influence LV mass or other echocardiographic parameters [2, 3]. We found that the persistence of even large, high-flow AV fistulas for prolonged periods of time did not significantly influence the LV mass and had little impact on cardiac morphology and function.…”
Section: Discussioncontrasting
confidence: 53%
“…Left ventricular (LV) hypertrophy is a well-established cardiovascular risk factor which is frequently observed in renal transplant recipients [1, 2, 3]. There is scant information on the cardiac effects of patent arteriovenous (AV) fistulas in recipients of renal transplants.…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling ʈData from Kasiske. 10 ¶Data from Parfrey et al, 11 Hernandez et al, 12 Peteiro et al, 13 Huting et al, 14 often accompanies a reduction in arterial compliance, which can be detected through measurement of aortic pulse wave velocity and characteristic impedance. 34,35 Noncompliant vessels may result in increased systolic blood pressure, increased pulse pressure, LVH, and decreased coronary perfusion.…”
Section: Spectrum Of Cvd In Ckd and Differences From The General Popumentioning
confidence: 99%
“…The prevalence of coronary artery disease is Ϸ15%, 10 the prevalence of LVH is 50% to 70%, [11][12][13][14][15] and the incidence of CVD is at least 3 to 5 times that of the general population. 6,10 Risk factors for CVD in kidney transplant recipients are multiple.…”
Section: Cvd In Kidney Transplant Recipientsmentioning
confidence: 99%
“…LVH is associated with increased mortality on hemodialysis (736) and peritoneal dialysis (738). Although LVH often improves after renal transplantation (739)(740)(741)(742), it nevertheless predicts a worse posttransplant outcome (741,742). Even in the absence of randomized controlled trials it is reasonable to conclude that correcting LVH in hemodialysis patients may reduce risk and improve outcomes while on the waiting list and after renal transplantation.…”
Section: Recommendationsmentioning
confidence: 99%